The Cubic polynomial f(x) is such that the coefficient of x ^ 3 is -1 and the zeros of f(x) are 1, 2 and k. If f (x) has a remainder of 8 when divided by x - 3 then find (1) the value of k (2) the remainder when f(x ) is divided by x + 3
Answers
Answered by
61
Answer:
1)k = 7
2)200
Step-by-step explanation:
Given the zeros of f(x) are 1,2 and k.
Any cubic polynomial with 3 roots p,q and r and leading coefficient a will be in the form
a(x-p)(x-q)(x-r) = 0
Given f(x) has leading coefficient -1 so a = -1
Given the zeros p =1 , q =2 and r = k
Hence f(x) will be of the form
f(x) = -(x-1)(x-2)(x-k)
Now, given that f(x) has remainder of 8 when divided by x-3
We know from Remainder's Theorem , when f(x) is divided by (x-a), then the remainder will be equal to f(a).
Hence f(3) = 8
But f(3) = -(2)(1)(3-k) = 8
=>3-k = -4
=>k = 7-----Ans
2)
So, f(x) = -(x-1)(x-2)(x-7)
Now, if f(x) is divided by (x+3), remainder will be equal to
=f(-3)
=-(-4)(-5)(-10)
=200.-----Ans
Answered by
17
Answer: k = -1
f(-3) = -40
Solution:
Standard cubic polynomial is given as
![a {x}^{3} + b {x}^{2} + cx + d \\ \\ given \: \: a = - 1 \\ \\ - 1 {x}^{3} + b {x}^{2} + cx + d \\ \\ a {x}^{3} + b {x}^{2} + cx + d \\ \\ given \: \: a = - 1 \\ \\ - 1 {x}^{3} + b {x}^{2} + cx + d \\ \\](https://tex.z-dn.net/?f=a+%7Bx%7D%5E%7B3%7D+%2B+b+%7Bx%7D%5E%7B2%7D+%2B+cx+%2B+d+%5C%5C+%5C%5C+given+%5C%3A+%5C%3A+a+%3D+-+1+%5C%5C+%5C%5C+-+1+%7Bx%7D%5E%7B3%7D+%2B+b+%7Bx%7D%5E%7B2%7D+%2B+cx+%2B+d+%5C%5C+%5C%5C+)
if
![\alpha \beta \gamma \alpha \beta \gamma](https://tex.z-dn.net/?f=+%5Calpha+%5Cbeta+%5Cgamma+)
are the roots of cubic polynomial
![\alpha = 1 \\ \\ \beta = 2 \\ \\ \gamma = k \\ \alpha = 1 \\ \\ \beta = 2 \\ \\ \gamma = k \\](https://tex.z-dn.net/?f=+%5Calpha+%3D+1+%5C%5C+%5C%5C+%5Cbeta+%3D+2+%5C%5C+%5C%5C+%5Cgamma+%3D+k+%5C%5C+)
![\alpha + \beta + \gamma = \frac{ - b}{a} \\ 3 + k = \frac{ - b}{a} \\ \\ 3 + k = b \\ \\ 2 + k + 2k = \frac{c}{a} \\ \\ 2 + 3k = \frac{c}{a} \\ \\ 2 + 3k = - 1 \\ \\ 2k = \frac{ - d}{a} \\ \\ 2k = d \alpha + \beta + \gamma = \frac{ - b}{a} \\ 3 + k = \frac{ - b}{a} \\ \\ 3 + k = b \\ \\ 2 + k + 2k = \frac{c}{a} \\ \\ 2 + 3k = \frac{c}{a} \\ \\ 2 + 3k = - 1 \\ \\ 2k = \frac{ - d}{a} \\ \\ 2k = d](https://tex.z-dn.net/?f=+%5Calpha+%2B+%5Cbeta+%2B+%5Cgamma+%3D+%5Cfrac%7B+-+b%7D%7Ba%7D+%5C%5C+3+%2B+k+%3D+%5Cfrac%7B+-+b%7D%7Ba%7D+%5C%5C+%5C%5C+3+%2B+k+%3D+b+%5C%5C+%5C%5C+2+%2B+k+%2B+2k+%3D+%5Cfrac%7Bc%7D%7Ba%7D+%5C%5C+%5C%5C+2+%2B+3k+%3D+%5Cfrac%7Bc%7D%7Ba%7D+%5C%5C+%5C%5C+2+%2B+3k+%3D+-+1+%5C%5C+%5C%5C+2k+%3D+%5Cfrac%7B+-+d%7D%7Ba%7D+%5C%5C+%5C%5C+2k+%3D+d)
cubic polynomial is
![{x}^{3} - (3 + k) {x}^{2} + (2 + 3k)x - 2k \\ \\ {x}^{3} - (3 + k) {x}^{2} + (2 + 3k)x - 2k \\ \\](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D+-+%283+%2B+k%29+%7Bx%7D%5E%7B2%7D+%2B+%282+%2B+3k%29x+-+2k+%5C%5C+%5C%5C+)
1) Now the polynomial had remainder 8 if divided by x-3
![x - 3){x}^{3} - (3 + k) {x}^{2} + (2 + 3k)x - 2k( {x}^{2} - kx + 2 \\ \: \: \: \: \: \: \: \: \: \: \: \: {x}^{3} - 3 {x}^{2} \\ - - - - - - - - \\ \: \: \: \: \: \: \: \: - k {x}^{2} + (2 + 3k)x \\ \: \: \: \: \: \: \: \: \: - k {x}^{2} + 3kx \\ \: \: \: - - - - - - - \\ \: \: \: \: \: \: \: \: \: 2x - 2k \\ \: \: \: \: \: \: \: \: \: 2x - 6 \\ - - - - - - - \\ \: \: \: \: \: \: \: \: \: \: - 2k + 6 \\ \\ x - 3){x}^{3} - (3 + k) {x}^{2} + (2 + 3k)x - 2k( {x}^{2} - kx + 2 \\ \: \: \: \: \: \: \: \: \: \: \: \: {x}^{3} - 3 {x}^{2} \\ - - - - - - - - \\ \: \: \: \: \: \: \: \: - k {x}^{2} + (2 + 3k)x \\ \: \: \: \: \: \: \: \: \: - k {x}^{2} + 3kx \\ \: \: \: - - - - - - - \\ \: \: \: \: \: \: \: \: \: 2x - 2k \\ \: \: \: \: \: \: \: \: \: 2x - 6 \\ - - - - - - - \\ \: \: \: \: \: \: \: \: \: \: - 2k + 6 \\ \\](https://tex.z-dn.net/?f=x+-+3%29%7Bx%7D%5E%7B3%7D+-+%283+%2B+k%29+%7Bx%7D%5E%7B2%7D+%2B+%282+%2B+3k%29x+-+2k%28+%7Bx%7D%5E%7B2%7D+-+kx+%2B+2+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%7Bx%7D%5E%7B3%7D+-+3+%7Bx%7D%5E%7B2%7D+%5C%5C+-+-+-+-+-+-+-+-+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+-+k+%7Bx%7D%5E%7B2%7D+%2B+%282+%2B+3k%29x+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+-+k+%7Bx%7D%5E%7B2%7D+%2B+3kx+%5C%5C+%5C%3A+%5C%3A+%5C%3A+-+-+-+-+-+-+-+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+2x+-+2k+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+2x+-+6+%5C%5C+-+-+-+-+-+-+-+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+-+2k+%2B+6+%5C%5C+%5C%5C+)
So
![- 2k + 6 = 8 \\ \\ - 2k = 2 \\ \\ k = - 1 \\ - 2k + 6 = 8 \\ \\ - 2k = 2 \\ \\ k = - 1 \\](https://tex.z-dn.net/?f=+-+2k+%2B+6+%3D+8+%5C%5C+%5C%5C+-+2k+%3D+2+%5C%5C+%5C%5C+k+%3D+-+1+%5C%5C+)
So the polynomial is
![{x}^{3} - (3 - 1) {x}^{2} + (2 - 3)x + 2 \\ \\ {x}^{3} - 2 {x}^{2} - x + 2 \\ {x}^{3} - (3 - 1) {x}^{2} + (2 - 3)x + 2 \\ \\ {x}^{3} - 2 {x}^{2} - x + 2 \\](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B3%7D+-+%283+-+1%29+%7Bx%7D%5E%7B2%7D+%2B+%282+-+3%29x+%2B+2+%5C%5C+%5C%5C+%7Bx%7D%5E%7B3%7D+-+2+%7Bx%7D%5E%7B2%7D+-+x+%2B+2+%5C%5C+)
2)
f(-3) = -40
Solution:
Standard cubic polynomial is given as
if
are the roots of cubic polynomial
cubic polynomial is
1) Now the polynomial had remainder 8 if divided by x-3
So
So the polynomial is
2)
Similar questions
Computer Science,
8 months ago
Biology,
8 months ago
Physics,
1 year ago
Computer Science,
1 year ago
Physics,
1 year ago
Social Sciences,
1 year ago